2021
DOI: 10.1002/ajmg.a.62185
|View full text |Cite
|
Sign up to set email alerts
|

Hemimegalencephaly and intractable seizures associated with the NPRL3 gene variant in a newborn: A case report

Abstract: Hemimegalencephaly (HME) is a rare hamartomatous congenital malformation of the brain characterized by dysplastic overgrowth of either one of the cerebral hemispheres. HME is associated with early onset seizures, abnormal neurological findings, and with subsequent cognitive and behavioral disabilities. Seizures associated with HME are often refractory to antiepileptic medications. Hemispherectomy is usually necessary to provide effective seizure control. The exact etiology of HME is not fully understood, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…Sirolimus treatment produced varied outcomes in two infants with NPRL3 ‐related hemimegalencephaly. One infant had reduced seizures but stopped treatment after 3.5 months due to recurrent infections [15], while the other stopped sirolimus after 17 days due to lack of efficacy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Sirolimus treatment produced varied outcomes in two infants with NPRL3 ‐related hemimegalencephaly. One infant had reduced seizures but stopped treatment after 3.5 months due to recurrent infections [15], while the other stopped sirolimus after 17 days due to lack of efficacy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Functional hemispherectomy at 3 months of age resulted in total abatement of clinical seizures. 7 Similarly, Kulkarni et al 5 reported a term infant with HME who had more than 90% reduction in seizures with good developmental outcome on follow-up after hemispherectomy. In addition, Chand and colleagues 8 reported a neonate who presented with focal seizures.…”
Section: Images In…mentioning
confidence: 95%
“…The intractable seizures in the context of this condition usually necessitate anatomical or functional hemispherectomy to provide effective seizure control. Chandrasekar and colleagues7 reported a female newborn who had refractory seizures due to HME. WES analysis revealed a likely pathogenic deletion involving the NPRL3 (nitrogen permease regulator 3-like protein) gene, which is involved in the mammalian target of rapamycin (MTOR) signalling pathway.…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases with simultaneous mutations in different GATOR1 genes have not been described thus far. Several Nprl2 or Nprl3 variants found in individuals with FCD or hemimegaloencephaly (HME) have been reported recently [184,185]. Interestingly, NPRL3 single nucleotide polymorphism has been associated with ischemic stroke susceptibility and post-stroke mortality [186], which can be related with increased mTOR activity, that is known to accelerate brain recovery after stroke.…”
Section: Epilepsies and Brain Malformations-depdc5 And Othersmentioning
confidence: 99%